Bridging Arabic Language Gap: Project-Based Learning through a Peer Tutoring for Pre-University Learners - Aji Rizqi Ramadhan; Asep Sopian; Uswah Mujahidah Rasuna Said; Arina Dienana; Irsyad Fadlurrahman (English Department FBS UNP, 2025)
This study aims to determine the effectiveness of implementing the Project-Based Learning (PjBL) model combined with the peer tutoring method in improving and bridging the gap in Arabic language proficiency among pre-university students. The method used is quantitative with a quasi-experimental design. The research sample comprised 48 pre-university students at The research sample comprised 48 pre-university students from one of the Islamic boarding schools in Indonesia. The research instruments included tests (descriptive statistical analysis, N-Gain test, and T-test) and a questionnaire. The experimental class's pre-test scores ranged from a minimum of 40 to a maximum of 74, with an average of 58.25, while the post-test scores showed a significant increase, ranging from 73 to 98, with an average of 86.29. The control class showed a lower improvement, with a pre-test average of 57.75 and a post-test average of 70.04. The N-Gain result for the experimental class was 69.07% (moderate category), while the control class scored 29.70% (low category), showing a difference of 39.37%. The T-Test results indicated a sig. (2-tailed) value of 0.000 < 0.05, demonstrating significant effectiveness in the experimental class. Student response toward implementing the PjBL model and peer tutoring reached 83.23%, which is considered positive. Therefore, the implementation of the PjBL model and peer tutoring method has proven effective in bridging the gap in students’ Arabic proficiency and in producing personalized vocabulary dictionaries.